Women’s Political Participation in the Practice of Citizenship in Indonesia - NFN Partini (Yayasan Jurnal Perempuan, 2014)
Women’s participation in politics is the manifestation of the citizenship right fulfillment. Women as well as vulnerable groups as citizens have the right to improve their existence in politics. The rights that attach to women as citizens hopefully can make them not only as the vote-getter or political parties’ participants but also as those being elected and exercise policy. Politic is genderless but politic system is constructed mostly by men. And women are lacking confidence within this culture of politic. It then deteriotes the stigma that women are unable and having no capacity to compete with men. Although women are legal citizens but the culture of politic is neither friendly to women nor conducive to feminine traits. The electoral process in citizenships system hopefully does not only create the man-represented view, but also a transformation process between the political party and the women platform.